(untitled) (Journal of Advanced Research in Social Sciences, 2024)
This paper begins from the premise that a key element in comprehending the discipline of International Relations lies in the understanding of state behaviour. This constitutes the main objective of this paper, which focuses on the limited scope of examining one aspect of state behaviour, foreign policy. Foreign policy is examined through the interconnected lenses of ideology and discourse. The argument developed is that ideology sustains foreign policy through the provision of the foundational support that it requires for its perpetuation and through the creation of an overarching narrative that not only explains, but also justifies foreign policy choices. In this context, the concepts of state identity and interests are elevated as two fundamental elements of state behaviour, which are narratively procured via ideology and define the aims of foreign policy and the means of pursuing them. The paper makes clear that the ideological underpinnings of foreign policy require the crucial contribution of discourse as an intervening variable that allows for the narrative performance of identity and the pursuit of foreign policy ends, dictated by identity. Security is conceptualised and exemplified through discourse, with the latter becoming an indispensable element not only of foreign policy, but also of state survival.